Well-being Siswa yang Diikutkan Banyak Kegiatan Bimbingan Belajar oleh Orang Tuanya - Ledya Mawaddah (International Consortium of Education and Culture Research Studies, 2018)
Psychological well-being (psychological well-being) is an important aspect that determines the quality of student learning. Not a few students in Indonesia that included tutoring by his parents more than two places tutoring. This research aims to provide a scientific idea against parents and teachers to be more attentive to the mental development of the students, in this case it is the psychological well-being of students. According to Piaget, learning that is incompatible with the child's cognitive development have negative consequences for the development of other psychological aspects. Including his tutoring is a good step to provide facilities at students in the Leisure and completing their learning difficulties, but not to the large number of tutoring followed by students (cognitive activities) is precisely make students are depressed and damaging the structure of the kognitifnya. Students must be given the space to play, develop a positive hobby, develop language skills and social interaction as well as other self development.